DESCRIPTION OF ENGLISH SYNTAX IN THE JAKARTA POST NEWSPAPER - Atmaja, Theodore Alexander; Sudarsono, Sudarsono; Regina, Regina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractLanguage available in a newspaper is consumed in a wide public or society so that the sentence structure available in a newspaper is usually constructed carefully according to the level of consumer or reader. Newspaper also plays the major role in accelerating language study. Newspaper sentence structures are composed from various types of tenses and various types of sentences. The research method apply for this is research is textual analysis since the research is analyzing the descriptive in the newspaper. After analyzing the sentence structure in The Jakarta Post newspaper, it is found that descriptive consists of 4 types of sentences and resulted in 371 sentences were found in total. The 371 sentences consist of 86 sentences in simple sentence, 74 sentences for compound sentence, 169 sentences for complex sentence and 42 for compound-complex sentence. The sentence structures found in Jakarta Post newspaper are well structured and recommended for further tool for studying reading for enhancement process.Â Keyword: Descriptive analysis, Grammar, Language, Newspaper, Sentence structure, The Jakarta Post.